The Indonesia National Survey Project 2022: Engaging with Developments in the Political, Economic and Social Spheres - Muhtadi, Burhanuddin; Hui, Yew-Foong; Negara, Siwage Dharma (ISEAS – Yusof Ishak Institute, 2023)
ISEAS - Yusof Ishak Institute has commissioned a second nationwide survey in Indonesia as a follow-up to the first similar project in 2017 called the Indonesia National Survey Project (INSP). Its broad aim is to enhance understanding of political, economic, and social developments in Indonesia.